Effect of EDTA Addition on Acidizing Treatment Process - Fitriyanti, Reno; Pandjaitan, M.M. Lanny W.; Lukas, Lukas; Harlis, Gilang Bagaskara; Wahyudi, Agus; Fatimura, Muhrinsyah (CHEESA: Chemical Engineering Research Articles, 2023)
Acidizing treatment is commonly used to solve scale problem on production equipment. In this process, Hydrochloric acid (HCl) is often used to treat CaCO3 scale, posing the risk of pipe corrosion due to its high corrosive characteristics. Thus, the purpose of this study was to determine the impact of adding EDTA additive into HCl solution during the acidifying treatment procedure. The methodology included various stages such as scale identification, chemical scale removal test using 7.5% and 15% HCL solution, 15% HCl solution test with EDTA as an additive, and corrosion determination using corrosion coupon. The results showed that 15% HCl solution was very effective in removing CaCO3 scale but had a high corrosion rate of 186.255 mpy. Furthermore, the addition of 10 mL EDTA solution as an additive removed scale and reduced corrosion rate by approximately 85%.